The First Protocol for Assessing Welfare of Camels - Padalino, Barbara; Menchetti, Laura (Frontiers in Veterinary Science, 2021)
The aim of this study was to develop and describe a protocol for assessing welfare in camels reared in intensive or semi-intensive systems. A literature review was conducted searching for scientific papers on assessment of animal welfare and camel behavior, management, physiology, and pathology. The paradigms of Five Freedoms, the Five Domains Model, and the welfare principles and criteria applied by the Welfare Quality® and AWIN methods were then adapted to camels. A combination of animal-, resource- and management-based indicators were selected and categorized according to three levels of assessment: (i) Caretaker, (ii) Herd, and (iii) Animal. The Caretaker level is an interview of 23 questions exploring the caretaker's background, experience, and routine management practices. The Herd level is a check of the herd and of the place (i.e., box/pen) where camels are kept. The Animal level is a visual inspection aiming at evaluating individual camel behavior and health status. The selected indicators are presented for each welfare principle and level; for instance for the principle of “Appropriate nutrition,” feeding management is investigated at Caretaker level; feed availability and quality, the number of feeding points, and camel feeding behavior are recorded at Herd level, while body condition score (BCS) is evaluated at Animal level. In this study recording sheets for the assessment at the three levels are proposed and how to conduct the assessment is described. Limitations of the proposed protocol are also discussed. Further applications of this protocol for assessing camel welfare on a large number of farms is needed to validate the proposed indicators and identify the thresholds for their acceptability as well as to develop overall welfare indices and welfare standards in camels.